Directional Oil Sliding Surfaces with Hierarchical Anisotropic Groove Microstructures. (5th August 2013) - Kang, Seong Min; Lee, Chanseok; Kim, Hong Nam; Lee, Byung Jun; Lee, Ji Eun; Kwak, Moon Kyu; Suh, Kahp‐Yang
<x xml:space="preserve">Abstract</x> A robust directional oil sliding surface is presented by utilizing re‐entrant micro‐groove arrays inspired from the microgrooves of rice leaf. The overhang micro‐groove arrays are shown to provide two primary goals of "omniphobicty" and "anisotropic sliding" with DI water (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3t136v0q" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γlv</alternatives> = 72.1 mN/m) as well as mineral oil (<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3t136tgx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />γlv</alternatives> = 28 mN/m) and conventional photoresist. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>